Genetic analysis of bleeding disorders. (July 2016) - Edison, E.; Konkle, B. A.; Goodeve, A. C.
Abstract : Molecular genetic analysis of inherited bleeding disorders has been practised for over 30 years. Technological changes have enabled advances, from analyses using extragenic linked markers to next‐generation DNA sequencing and microarray analysis. Two approaches for genetic analysis are described, each suiting their environment. The Christian Medical Centre in Vellore, India, uses conformation‐sensitive gel electrophoresis mutation screening of multiplexed PCR products to identify candidate mutations, followed by Sanger sequencing confirmation of variants identified. Specific analyses for F8 intron 1 and 22 inversions are also undertaken. The MyLifeOurFuture US project between the American Thrombosis and Hemostasis Network, the National Hemophilia Foundation, Bloodworks Northwest and Biogen uses molecular inversion probes (MIP) to capture target exons, splice sites plus 5′ and 3′ sequences and to detect F8 intron 1 and 22 inversions. This allows screening for all F8 and F9 variants in one sequencing run of multiple samples (196 or 392). Sequence variants identified are subsequently confirmed by a diagnostic laboratory. After having identified variants in genes of interest through these processes, a systematic procedure determining their likely pathogenicity should be applied. Several scientific societies have prepared guidelines. Systematic analysis of the available evidence facilitates reproducible scoring of likely pathogenicity. Documentation of frequency in population databases of variant prevalence and in locus‐specific mutation databases can provide initial information on likely pathogenicity. Whereas null mutations are often pathogenic, missense and splice site variants often require in silico analyses to predict likely pathogenicity and using an accepted suite of tools can help standardize their documentation.